(untitled) (Medico Legal Update, 2020)
In this fast paced global world, human being is surrounded by numerous tensions and various competitors. To survive in this complex world one has to put his whole and sole effort to earn his livelihood. For this he has to do millions of work which causes stress. So employees need to manage stress and remove their occupational illness. The objective of this research is to determine how occupational health psychology is being handled in IT industry. Along with that I will analyze the importance of stress management from the organizations point of view, identify reasons, effects and stress release strategies. I have used primary data of the IT industry to study how health and safety measures can be taken to remove the mental and physical illness of employees in IT sector. Secondary data is also used for analysis purpose.